UJI BEBERAPA KONSENTRASI EKSTRAK TEPUNG DAUN BABADOTAN (Ageratum conyzoides L.) TERHADAP HAMA PENGGEREK TONGKOL JAGUNG (Helicoverpa armigera Hubner) DI LABORATORIUM - Melisa Eka Nofrianti; Desita Salbiah (DINAMIKA PERTANIAN, 2022)
The main pest that attacks the sweet corn plant is the sweet corn cobs mover (Helicoverpa armigera Hubner. Pest control can be done by using botanical insecticide babadotan plants (Ageratum conyzoides L.). The aim of this research was to get a effective concentration of babadotan leaf flour extract against H. armigera larvae in the Laboratory. The research was conducted at the Plant Pest Laboratory, Faculty of Agriculture, University of Riau. The research used a completely randomized design (CRD) with five treatments and four replications. The treatments were given several concentrations of babadotan leaf flour extract 0%, 0.25%, 0.50%, 0.75% and 1%. The parameters observed were changes in behavior and morphology, initial time of death (hours), Lethal time 50 (hours), daily mortality (%), total mortality (%), and Lethal concentration (%). Variance results were further tested with Duncan's New Multiple Range Test (DNMRT) at a 5% level. The results showed that the concentration of 0.75% babadotan leaf flour extract was an effective concentration that could cause total mortality of H. armigera larvae at 82.50% with an initial time of death of 8.75 hours and a Lethal time of 50 of 42.75 hours after application. The proper concentration of babadotan leaf extract to kill 50% and 95% was 0.11% that is equivalent to 1.1 ml.1-1 of water and 3.29% that equivalent to 32.9 ml.l-1 of water.